interfunktionen no. 11 : Zeitschrift für neue Arbeiten und Vorstellungen. (Köln : B.H.D. Buchloh, 1974)
Immendorff, Jörg ; Penck, A.R. ; Jakobson, Roman ; Weiner, Lawrence ; Broodthaers, Marcel ; Claura, Michel ; Celant, Germano ; Graham, Dan ; Buren, Daniel ; Nauman, Bruce ; Scanga, Italo ; Beckley, Bill
boek